2008
DOI: 10.1002/ajim.20566
|View full text |Cite
|
Sign up to set email alerts
|

Rye flour allergens: An emerging role in baker's asthma

Abstract: Both bakers had developed occupational asthma to rye flour (confirmed by specific inhalation challenge test). Rye flour allergens (enzymatic inhibitors) are important allergens that should be considered in the diagnosis of baker's asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…Consistent with other studies [3,26,27,28], respiratory symptoms were found to be significantly more prevalent among exposed subjects (Table 2). Similarly, occupational exposure to flour dust has been reported to lead to reduction of ventilatory capacities [12,13,14,15,16,17]. In accordance with these findings, we have shown that exposure to flour dust resulted in significant reductions in some parameters of pulmonary function such as VC, FVC, FEV 1 , FEV 1 /FVC ratio and PEF.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with other studies [3,26,27,28], respiratory symptoms were found to be significantly more prevalent among exposed subjects (Table 2). Similarly, occupational exposure to flour dust has been reported to lead to reduction of ventilatory capacities [12,13,14,15,16,17]. In accordance with these findings, we have shown that exposure to flour dust resulted in significant reductions in some parameters of pulmonary function such as VC, FVC, FEV 1 , FEV 1 /FVC ratio and PEF.…”
Section: Discussionsupporting
confidence: 80%
“…They also have a higher degree of nonspecific bronchial responsiveness than control workers [9,10] and exhibit greater variability of lung function during the work week [9]. Studies of occupational exposure to flour dust with pulmonary function tests have shown significant decreases in lung function parameters such as forced vital capacity (FVC), forced expiratory volume in the first second (FEV 1 ), peak expiratory flow (PEF) and maximum voluntary ventilation [12,13,14,15,16,17]. Currently, more than 14 million tonnes of wheat are produced and used, annually, in Iran [18].…”
Section: Introductionmentioning
confidence: 99%
“…The test was performed using an electronic dosimeter (Spire Elektro, Respiratory Care Center, Hameelinna, Finland) with an output of 0.45 ll and a nebulization time of 0.6 s as previously described [23]. The patient inhaled the aerosolized allergen using a fivebreath dosimeter protocol in progressive concentrations [24].…”
Section: Bronchial Allergen Challengementioning
confidence: 99%
“…Notwithstanding this limitation, 6 of the 43 studies lacking cross‐tabulation (plus all four studies lacking objective pulmonary function tests) provided partial associational data, in which either: 1) the proportion of (presumed) occupational rhinitis cases developing occupational asthma (or vice versa) is reported (albeit in the absence of background rates); or 2) the sequence of development of nasal and chest symptoms are tabulated. Individual study characteristics of excluded studies, including study designs, principal exposure(s), health endpoint(s), number of subjects, and measure(s) of effect appear in Supplemental Tables S1‐S4. Briefly summarizing relevant data from these excluded studies, among workers undergoing objective pulmonary function testing, more than half of those diagnosed with occupational asthma to diphenylmethane diisocyanate (MDI), lupin ( Lupinus angustifolius ) flour, or ammonium persulfate (eg, hairdressers) also gave histories consistent with occupational rhinitis .…”
Section: Resultsmentioning
confidence: 99%